Measurement, instrumentation, and sensors handbook : electromagnetic, optical, radiation, chemical, and biomedical measurement - Webster, John G., 1932-; Eren, Halit (Professor of electrical engineering) (Boca Raton : CRC Press, Taylor & Francis Group, 2014)
"The Second Edition of the bestselling Measurement, Instrumentation, and Sensors Handbook brings together all aspects of the design and implementation of measurement, instrumentation, and sensors. Reflecting the current state of the art, it describes the use of instruments and techniques for performing practical measurements in engineering, physics, chemistry, and the life sciences and discusses processing systems, automatic data acquisition, reduction and analysis, operation characteristics, accuracy, errors, calibrations, and the incorporation of standards for control purposes. Organized according to measurement problem, the Electromagnetic, Optical, Radiation, Chemical, and Biomedical Measurement volume of the Second Edition contains contributions from field experts, new chapters, and updates to all 98 existing chapters. Covers sensors and sensor technology, time and frequency, signal processing, displays and recorders, and optical, medical, biomedical, health, environmental, electrical, electromagnetic, and chemical variables. A concise and useful reference for engineers, scientists, academic faculty, students, designers, managers, and industry professionals involved in instrumentation and measurement research and development, Measurement, Instrumentation, and Sensors Handbook, Second Edition: Electromagnetic, Optical, Radiation, Chemical, and Biomedical Measurement provides readers with a greater understanding of advanced applications"--
62. Patient-care sensing and monitoring systems -- 63. Sensor-based activity recognition techniques -- 64. Biopotentials and electrophysiology measurement -- 65. Blood pressure measurement -- Blood flow measurements -- 67. Medical imaging -- 68. Blood chemistry measurement -- 69. Human occupancy detectors -- Part VIII: Environmental: 70. GPR principles and applications -- 71. Airborne radiometers to measure electromagnetic radiation in the earth's atmosphere: mature and emerging technologies -- 72. In situ sensors for monitoring the marine environment -- 73. Mobile environmental sensing using smartphones -- 74. Space dosimetry -- 75. Capacitance sensors for nondestructive moisture determination in agricultural products and biofuel materials -- 76. Radio location, radio navigation, and GPS systems -- 77. Air pollution monitoring -- 78. Water quality measurement -- 79. Satellite imaging and sensing -- 80. Humidity and moisture measurement -- 81. Ventilation measurement -- 82. Meteorological measurement -- 83. Robotics and sensors: environmental applications -- Part IX: Signal Processing: 84. Modulation -- 85. Filters -- 86. Spectrum analysis and correlation -- 87. Applied intelligence processing -- 88. Analog-to-digital converters -- 89. Computers -- 90. Grounding and shielding -- 91. Amplifiers and signal conditioners -- 92. Data acquisition systems -- Part X: Displays and Recorders: 93. Plasma-driven flat panel displays -- 94. Electroluminescent displays -- 95. Light-emitting diode displays -- 96. Magnetic and optical recording -- 97. Liquid crystal displays -- 98. Cathode ray tube displays -- Appendix: Units and conversions
Includes bibliographical references and index
Keywords: Physical measurements -- Handbooks, manuals, etc; Measurement -- Handbooks, manuals, etc; Scientific apparatus and instruments -- Handbooks, manuals, etc; Handbooks and manuals